O trabalho pedagógico da educação física na escola Roseli Correa da Silva: um estudo de caso - Charão, Carine Marques (2017)
This dissertation is inserted in socio-cultural and pedagogical aspects research line, located in the postgraduate program of the Center for Physical Education and Sports (CEFD) of UFSM. It has a deep relation with the researcher's experiences acting in the countryside education of Rio Grande do Sul education network. It aims to understand how the pedagogical work of Physical Education is constituted, concerning the pedagogical theory, in the State School of Elementary Education Roseli Correa da Silva (RCS). The context of the research takes place at Nova Santiago settlement, also known as Santa Rita, as it is called by the settlers / residents, where the School (RCS) is located, in the city of Capão do Cipó. The school was created in 1988, one year after the families settled in, which came mostly from the Anoni ranch camp, in 1985. It is a case-study research using historical and dialectical materialism as theoretical foundation. In this sense, after the investigative course, we confirmed the hypothesis raised in the study, that the MST and consequently the settlement school and the physical education pedagogical work , through the pedagogical theory, has been moving away from the principles that initially guided the countryside education and inspired the first struggles to occupy the land. However, the MST (No Land Workers Movement), in Brazil, and perhaps even outside it, assumes a fundamental political importance, mainly in the 1990s, as a strong contrast to neoliberal educational policies, forging a stir in the dispute of projects for the Brazilian countryside. We reinforce, as already mentioned in the text of the study, the importance of the theory of historical and dialectical materialism, as a foundation for pedagogical theory, which also supports physical education.